TRANSFORMASI RUANG AKIBAT KONFLIK: (Studi Kasus: Kawasan Wisata Kuta, Bali) - Agung Wahyudi; Imam Buchori; Joesron Alie Sjahbana (Jurnal Koridor, 2019)
The transformation of space in architecture due to conflicts of interest, has not been studied much, so that architecture is used as a benchmark for understanding quality, marking the ownership or power of a group towards space. With a case study of conflicts of interest in the Kuta Bali tourist area, and by applying the land reconstruction method, it was found a process of changing space and its impact on the people of Kuta in particular and for Bali tourism in general, because Kuta is a major tourist destination. In this study will refine the theory of the description of architectural processes of space change due to conflicts of interest. Findings about inter-disciplinary research methods, bridging architectural science with its supporting sciences (sociology, psychology, anthropology). The role of architecture will support an alternative concept in the process of changing space due to conflicts of interest, as well as spatial planning that experiences dynamic and multi-dimensionalchanges.